Evaluasi Kebijakan Pengelolaan Sampah Berbasis Sumber di Desa Adat Bindu, Kecamatan Abiansemal, Kabupaten Badung - I Gusti Ayu Dwira Angganita (Public Inspiration : Jurnal Administrasi Publik, 2025)
This study aims to evaluate the implementation of source-based waste management policy at the Reduce, Reuse, and Recycle (3R) Waste Processing Facility in Bindu Traditional Village, Abiansemal District, Badung Regency. The research employs a qualitative descriptive approach, utilizing observation, interviews, and documentation as data collection techniques. Informants were selected through purposive sampling, totaling eight individuals. The findings indicate that the implementation of source-based waste management policy has been effectively carried out, as evidenced by the comprehensive waste processing system, with no residual waste being sent to the final disposal site (TPA), and the creation of a clean environment. However, the aspects of efficiency and responsiveness remain suboptimal. The implementation of this policy has generated positive impacts on the community, particularly in improving environmental cleanliness and public welfare. The study recommends strengthening collaboration with stakeholders to ensure program sustainability, optimize the achievement of policy objectives, and reduce dependency on government assistance.